Starting with Sight: A Conversation between Rosemary Lee and Anna Heighway - Lee, Rosemary; Heighway, Anna (The International Journal of Screendance, 2017)
Words from a conversation between Rosemary Lee and Anna Heighway. The chat centres on Rosemary's practice, Liquid Gold is the Air and what it means to be a "visual" choreographer.